The Influence of Brand Experience, Perceived Value, Brand Personality, Brand Image, Product Quality and Service Quality on Brand Loyalty with Brand Trust as a Mediating Variable - Celyn, Joy; Hasan, Golan (Perpustakaan dan Penerbitan Unismuh Makassar, 2023)
This research was conducted with the aim of proving brand experience, perceived value, brand personality, brand image, product quality and service quality on brand loyalty with brand trust as a mediating variable among brand cellphone users in the city of Batam. The population in this research are Batam people who use smartphones. The purposive sampling method was used to collect samples by taking samples based on certain considerations, namely respondents who used smartphones. The smartphone brand is currently held by several brands, namely Xiaomi, Oppo, Samsung, Realme, Vivo, iPhone, and others. There are 35 questions in this research, so the minimum sample size required is 35 x 10 = 350 samples. Data was processed using the Smart Partial Least Square (PLS) 3.0 program. The results of this research show that the independent variable for the brand trust mediation variable is 0.553, which means that the independent variable can explain 55.3% of the mediation variable, while 44.7% is explained by other variables. The independent variable can explain the dependent variable as much as 80.3%. Meanwhile, 19.7% is explained by other variables. The results of the quality index are declared large because the GOF value is greater than 0.36.